IMPLEMENTATION OF COOPERATION WITH THE DEFENSE INDUSTRY OF INDONESIA AND THE NETHERLANDS IN IMPROVING MARITIME STRENGTH : (CASE STUDY: PKR 10514) - Rifqi Muarief (Jurnal Teknik Industri, Sistem Informasi dan Teknik Informatika, 2022)
This study aims to discuss the cooperation of the Indonesian and Dutch defense industries in the manufacture of warships as defense equipment with the latest technology for the Indonesian Navy. The selection of the Netherlands as a cooperation partner is because the Netherlands is one of the countries with advanced technology in shipbuilding. This collaboration runs the Technology Transfer program in the construction of the PKR warship. In this study using the concept of an international regime. This study uses a descriptive qualitative approach and the data used are interviews and documentation. The results of this study conclude that the defense cooperation between Indonesia and the Netherlands is through technology transfer which passes through several stages, namely starting from the signing of the contract, the production process and the delivery of the PKR ship. The results of this defense cooperation, can help to strengthen the defense posture of the Indonesian Navy